SLMAP3 Governs Embryogenesis Through Mechanisms That Involve Centrosomal Dynamics as Exemplified in Developing Muscle - Dias, Ana (Université d'Ottawa | University of Ottawa, 2024)
SLMAP3 is a tail-anchored membrane protein that targets the microtubule-organizing center (MTOC), subcellular membranes, and is a component of the evolutionary conserved Striatin-Interacting Phosphatase and Kinase (STRIPAK) Complex. In this complex, SLMAP3 was demonstrated to inhibit Hippo signaling, leading to the expression of genes for cell proliferation in Drosophila and human cells. Here I investigated the in vivo roles of SLMAP by employing a mouse model that we generated with global ablation of the SLMAP3. These mice presented major deficits in organ development, leading to embryonic/perinatal lethality consistent with those reported for aberrant Planar Cell Polarity (PCP). These mice also exhibited polycystic kidneys, which is a common manifestation of ciliopathies, and abnormal embryonic muscle fibers with perturbation in distribution of their nuclei. RNA-seq indicated a repression of the myogenic program in SLMAP3 null embryos, and CRISPR/Cas9 mediated knockout of SLMAP3 in myoblasts resulted in defective differentiation and a clearly impaired recruitment of centrosomal proteins to the nuclear envelope, a process crucial for myogenesis. The loss of SLMAP3 affected the cell cycle dynamics including senescence in myoblasts. Cellular senescence was also observed in heart cardiomyoblasts with depletion of all SLMAP isoforms. Further, mouse embryonic fibroblasts (MEFs) isolated from SLMAP3-/- embryos had reduced primary cilia formation, which was accompanied by decreased protein levels of DVL3, a PCP member. SLMAP3 loss had no impact on Hippo pathway, and my data here reveals an entirely new mode for SLMAP action in development involving the MTOC, Cilia, PCP components and cell cycle dynamics.
Keywords: SLMAP3; Primary Cilium; MTOC; STRIPAK; PCP; Embryonic Development